CMOS-based current-controlled DDCC and its applications to capacitance multiplier and universal filter - Prommee, Pipat; Somdunyakanok, Montri (My University, 2011)
This paper presents design of an active building block for analog signal processing, named as current-controlled differential difference current conveyor (CCDDCC). Its parasitic resistances at X-terminal can be controlled by an input bias current. The proposed element is realized in a CMOS technology. It displays usability of the new active element, where the maximum bandwidth of voltage and current followers are around 1 GHz, 100 MHz, respectively. The THD is obtained around 0.8% within 0.6 Vpp input range. The power dissipation of a CCDDCC at 10μA biased current is obtained around 1.35 mW with ±1.25V power supplies. In addition, grounded capacitor-based floating capacitance multiplier and current-mode (CM) multiple-input single output (MISO) second-order universal analog filters are included as the applications. For realization of a grounded capacitor-based floating capacitance multiplier, it employs three CCDDCCs and one grounded capacitor without resistor connections. The capacitance can be tuned electronically through the bias current. The filter offers the simultaneous realization five type standard filter responses. The quality factor and the frequency response parameters can be independently tuned. The non-ideal effects of the developed structures are examined. SPICE simulation results of proposed CCDDCC and its applications are also presented. © 2009 Elsevier GmbH. All rights reserved.
Keywords: Current conveyors; Current-controlled differential difference current conveyors (CCDDCC); Current-mode filters